2015
DOI: 10.5812/ircmj.18293
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of Multiple Sclerosis Patients and Their Families: A Qualitative Study in Iran

Abstract: Background:Multiple Sclerosis (MS) is a neurological disease that is most commonly observed among young people. Drug and non-drug treatments are used to prevent the progression of the disease and to control illness-related disorders. Patients with MS often have multiple and complicated needs that require a broad spectrum of health services.Objectives:This study was conducted to identify the expectations of individuals with MS and their families for healthcare services.Patients and Methods:This article is part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
0
10
0
7
Order By: Relevance
“…In Iran, MS is a relatively rare and unknown condition and majority of Iranians do not know about associated compilations or what type of care is needed to manage MS [ 26 ]. This qualitative study was conducted to explore and describe family caregivers' understanding, experiences, and coping strategies when caring for persons with MS.…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, MS is a relatively rare and unknown condition and majority of Iranians do not know about associated compilations or what type of care is needed to manage MS [ 26 ]. This qualitative study was conducted to explore and describe family caregivers' understanding, experiences, and coping strategies when caring for persons with MS.…”
Section: Introductionmentioning
confidence: 99%
“…This situation may be led to stress, role captivity, and even the cessation of caregiving [34]. The studies in other parts of the world have had similar reports regarding the care of chronic and disabling diseases and financial burdens [17,19,20].…”
Section: Discussionmentioning
confidence: 50%
“…On the other hand, patients, their spouses and family members face numerous challenges such as losing a job, reduced income, changes in social status, and caregiver exhaustion [15]. Other studies have reported the effects of MS on economic setbacks and overall family welfare and suggested mental relaxation for family members as they learn to adapt to the disease progress, financial loss due to unemployment, and meeting the needs for additional expenses related to transportation and medical devices for patient mobility [16,17]. Economic impacts originate from patient's inability to work, hospitalization, and medical device for daily activities and costly medications for the disease management [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The stated factors together with sources of social support from families, life partners and other patients with MS contribute not only to maintaining dignity, but also to disease management and decrease of stress rate and improve their physical and psychological well-being. They can alleviate their symptoms and improve their adherence to treatment and life expectancy (Abolhassani et al, 2015;Dehghani, Dehghan Nayeri, Ebadi, 2018). Communication proves to be important, even central component affecting maintaining dignity (Lohne et al, 2010).…”
Section: Discussionmentioning
confidence: 99%